2018
DOI: 10.4103/sajc.sajc_188_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valproic acid on survival in glioblastoma: A prospective single-arm study

Abstract: Background:Retrospective evidence suggests that valproic acid (VPA), an antiepileptic drug, is associated with improved outcomes in glioblastoma. The exact mechanism of interaction of VPA with radiation and temozolomide (TMZ) is still unclear. Laboratory studies show that VPA can enhance tumor cell kill while at the same time protect the normal neural tissue. The aim of this study was to prospectively evaluate the benefit of VPA on outcomes in glioblastoma.Materials and Methods:In this single-arm prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Evidence from clinical studies suggest that VPA is significantly linked to improved outcome in GBM patients; although the mechanism of VPA interaction with mainstay treatments is unclear, synergy is clear between VPA, TMZ and radiation. Invitro lab studies confirm clinical findings and demonstrate that VPA can induce tumour cell death, whilst preserving healthy brain tissue [ 111 ].…”
Section: Ion Channel Inhibitors As Therapeutic Targetsmentioning
confidence: 75%
See 1 more Smart Citation
“…Evidence from clinical studies suggest that VPA is significantly linked to improved outcome in GBM patients; although the mechanism of VPA interaction with mainstay treatments is unclear, synergy is clear between VPA, TMZ and radiation. Invitro lab studies confirm clinical findings and demonstrate that VPA can induce tumour cell death, whilst preserving healthy brain tissue [ 111 ].…”
Section: Ion Channel Inhibitors As Therapeutic Targetsmentioning
confidence: 75%
“… Channel Tumour Drug References Cav3.2 GSC Mibefradil [ 92 ] Cav1.1, Cav1.2, Cav1.3, Cav1.4 Rat Derived GBM GBM mouse models GBM cell lines Pimozide Fluspirilene [ 107 , 108 , 109 ] Nav1.1 and Nav1.2. Human GBM Valporate Levetiracetam [ 110 , 111 , 112 ] Nav1.4 and Nav1.5 GBM cell line Riluzole [ 113 , 114 ] Kv1.4 GBM cell line Tamoxifen [ 115 ] Kv1.3 Human and mouse GBM biopsies Clofazimine [ 116 , 117 ] EAG1 Glioma Imipramine [ 118 , 119 ] …”
Section: Ion Channel Inhibitors As Therapeutic Targetsmentioning
confidence: 99%
“…Levetiracetam is now the most frequently prescribed drug for brain tumor-related epilepsy, followed by valproic acid [70,71]. Although multiple retrospective clinical studies stated improved outcome of patients with newly diagnosed glioblastoma after the addition of valproic acid [73,74,75,76,77,78,79,80,81] or levetiracetam [82] to standard therapy, while others did not reveal a significant effect on overall survival [70,75,83,84,85,86,87], the analysis of the prospective phase III clinical trials with a pooled cohort of 1869 patients demonstrated that levetiracetam or valproic acid did not influence median overall survival on multivariate analysis [88]. No significant impact on overall survival of patients with glioblastoma was also documented for other anti-epileptic drug [70].…”
Section: Standard Therapy For Adult Glioblastoma: 15 Years Of Expementioning
confidence: 99%
“…16,17 Previous studies showed that the separate use of TRAIL or PTEN has only limited antitumor effect on gliomas, [18][19][20][21] and the clinical trials have revealed only little therapeutic benefit. 5 During the past twenty years, various targeted therapies have been explored to treat GBM based on the study of genomic tools, such as inhibitors of multiple tyrosine kinase pathways, 22 poly (ADP-ribose) polymerase 1/2 (PARP1/2) inhibitors, 23 mTOR inhibitors, 24 histone deacetylase inhibitors, 25,26 and proteasome inhibitors. 27,28 But these treatments are unable to target the GBM patients' genomic and molecular characteristics sufficiently.…”
Section: Introductionmentioning
confidence: 99%